Study of nonlinear evolution of tearing modes induced by anomalous electron viscosity. (19th November 2015) - He, Zhixiong; Dong, J Q; He, Hongda; Wang, Z T; Long, Y X; Mou, Z Z
Abstract: The nonlinear development of double tearing modes (DTMs) induced by anomalous electron viscosity, which may be present in magnetically confined plasmas due to electromagnetic turbulence and structures such as braiding of magnetic field lines, in a periodic cylinder is simulated. Comparing the evolution of the helical magnetic flux contours, the nonlinear development of magnetic reconnection of the DTMs is studied for different distances between the two resonant rational flux surfaces. There are three clear phases in the nonlinear evolution of DTMs when the distance between the two resonant flux surfaces is large: linear growing, nonlinearly driven growing, and saturation. There are four phases when the distance is medium: linear growing, nonlinearly driven growing, fast growing, and decaying. Finally, there are three phases of evolution when the distance is quite small, which are different from the phases when the distance is large: linear growing, nonlinearly driven growing, and decaying, . The coupling between the fastest-growing modes at the two resonant surfaces drives the nonlinear evolution of the system.